Accuracies of Serum and Fecal S100 Proteins (Calprotectin and Calgranulin C) to Predict the Response to TNF Antagonists in Patients with Crohn's Disease. Issue 2 (February 2015) - Boschetti, Gilles; Garnero, Patrick; Moussata, Driffa; Cuerq, Charlotte; Préaudat, Corinne; Duclaux-Loras, Remi; Mialon, Anne; Drai, Jocelyne; Flourié, Bernard; Nancey, Stephane
Abstract : Background: Calprotectin and S100A12 (calgranulin C) are markers of gut inflammation. The aim was to compare the usefulness of serum and fecal calprotectin (fCal) and S100A12 in assessing the response to anti-TNF and in predicting relapse under maintenance therapy in Crohn's diseases (CD). Methods: Thirty-two consecutive patients with CD were treated with adalimumab or infliximab. All received an induction regimen followed by maintenance therapy with infliximab 5 mg/kg every 8 weeks or adalimumab 40 mg every other week and provided at week 0 and 14 fecal and blood samples for determination serum CRP, serum and fecal calprotectin and S100A12 levels. Results: Clinical remission at week 14 (responders) was achieved in 21 patients and among them, 12 were still in steroid-free clinical remission at week 52. Median serum S100A12 and fCal concentrations significantly drop only in responders from week 0 to week 14 after induction, whereas serum calprotectin and fecal S100A12 levels failed to differ significantly. Fecal calprotectin levels at week 14 had the highest discriminant validity to predict clinical remission within 1 year after induction (area under the curve = 0.87) followed by fecal, serum S100A12, and serum calprotectin (area under the ROC curve = 0.70, 0.70, and 0.68, respectively). A cutoff of 82 μg/g for fCal at week 14 had a sensitivity and specificity of 93% and 75%, respectively, to predict clinical remission within 1 year of therapy. Conclusions: Serum S100A12 level and fCal are reliable markers associated with response to induction therapy with anti-TNF. Fecal calprotectin was the best for predicting clinical remission in CD under maintenance therapy. Abstract : Article first published online 3 December 2014.